CONTRIBUTION OF ROYAL MUGHAL LADIES IN THE FIELD OF ART AND ARCHITECTURE FROM 1526-1707 A.D: A BRIEF SURVEY - Rehman Ganie, Zahied (International Journal of Research -GRANTHAALAYAH, 2018)
Indian woman since ancient days had played an important role in the socio-cultural and philosophical development of the country. Especially in Medieval India, the royal ladies of the Mughal court were almost as remarkable as their male counterparts. Royal Mughal ladies like Hamida Banu Begam, Haji Begam, Nurjahan Begam, Jahanara Begam, Roshanara Begam, Zeb-un-Nisa Begum etc. not only played a dominant role in contemporary politics but also contributed a lot to artistic field. The present article is an attempt to highlight the contribution of Royal Mughal ladies especially in Artistic field.